Panorametric study in a paediatric population in Madrid - Pérez de Mora, Esther; Caleya, Antonia M.; Martin Vacas, Andrea; Ginés Pérez, Ainara; de Nova García, Manuel Joaquín; Gallardo López, Nuría E. (My University, 2024)
The aim of the study was to establish the normality ranges of the linear and angular measurements that can be carried out in orthopantomographies (OPGs) of a paediatric sample from Madrid, according to sex and dentition. OPGs performed in the Radiology Service of the Faculty of Dentistry of the Complutense University of Madrid (UCM) from caucasic children between 4¿14 years old were selected. A total of 44 measurements were made in the OPGs, and the sex and type of dentition of each child were recorded. Panoramic Mandibular Index and Antegonial Index were also calculated. Statistical tests were performed with a confidence level of 95% (p < 0.05) and bilateral significance to analyse the differences between sex and type of dentition, and the correlation between the measurements of the right and left sides. A total sample of 160 OPGs (50% boys, 50% girls) were analysed. 16.25% of the sample was in primary dentition, 50% in first phase mixed dentition, 17.5% in second phase mixed dentition and 16.25% in permanent dentition. Statistically significant differences were found with respect to the sex of the subjects in 11 of the measurements¿ and 44 in relation to the dentition stages of the subjects. A strong correlation is found between the measurements on the right and left sides. The application of panoramic measurements as indicators of normality can help in the detection of craniofacial alterations in growth and development of the lower facial third. Keywords Pantomography¿ Orthopantomography¿ Panoramic radiography¿ Anatomy¿ Growth¿ Developmen